(untitled) (American International Journal of Sciences and Engineering Research, 2021)
Sustainable energy is the unconventional way that helps us to produce unlimited energy for ourselves so that we can use it without harming the environment. Of all renewable sources, Solar energy source is only one unlimited source that is environment friendly and has zero greenhouse effect. The solar cell is one way to collect solar photon energy and convert this energy into electrical energy that has already been invented. In this paper, we are trying to boost the solar output voltage by using the boost converter circuit. This paper proposes to boost the low voltage of the photovoltaic array by using the boost converter circuit and gain a higher output voltage. This paper investigates the modeling and simulating the photovoltaic module using MATLAB simulation along with the boost converter that will give the 95 % efficiency from the previous model. When investigating the maximum Power Point Tracking (MPPT) algorithms have improved for better efficiency.